Historical and Cultural Implications of Bogomilism - Angelovska-Panova, Maja ca. 20./21. Jh. (Occasional papers on religion in Eastern Europe, 2016)
Bogomilism represents a spiritual manifestation, dualistic in nature, of a religious expression, and a social and philosophical orientation. The essence of Bogomilism can be followed on the basis of several key postulates, such as dualism, a specific theological and dogmatic characteristic, the support of ethical principles within their social life, and finally the political dimension of teaching the determinants which rise from the overall social and political processes in medieval times. The aim of this article is to present the historical and cultural aspects of this movement, which left visible traces in the spiritual culture of Macedonia, Balkans, and Byzantium.